The dependence of milk yield on the living weight of cows of Simmental breed - F.R Sattarov; M.E Ashirov; F.B. Bahriddinov (International Consortium of Education and Culture Research Studies, 2020)
Studies have found that increasing the salinity of dairy cows with Simmental breeds in the herd is important in increasing milk production and creating high-yielding herds. The amount of milk of the cows having 531-560 kg live weight with the type of milk production was 768-1153 kg (P>0,999), milk fat output was 21.6-27.9 kg, 4% milk volume was 540,3-697.1 kg) higher than the different living weight Equinox with the type of milk-meat, and these indicators were determined as 932.5-1401.3 kg), 26.9-38.5 kg.